ABCG2 polymorphism, age and leukocyte count may contribute to oral mucositis in oncopediatric patients - Viana Filho,José Maria Chagas (2021)
Abstract The study investigated the relationship between genetic polymorphisms and the development of oral mucositis in pediatric patients undergoing chemotherapy involving methotrexate. A longitudinal study was conducted with 64 patients, and oral mucositis was evaluated by the modified Oral Assessment Guide, which aims to diagnose and classify oral mucositis. Epithelial cells were obtained by mouthwash and DNA was extracted. The polymorphisms MTHFR (rs1801133), DNMT3B (rs2424913), ABCC2 (rs717620), ABCG2 (rs2231137) and ABCG2 (rs2231142) were analyzed by PCR-RFLP method. Demographic, hematological and biochemical data were collected from medical records. Statistical analysis was performed using the SPSS software adopting a p-value of 0.05. Male sex predominated (56.2%), and the mean age was 10.8 years (± 4.9). Oral mucositis affected 65.6% of the patients, of which 61.9% developed the severe form of the disease. For the ABCG2 gene (rs2231142), the rare A allele and CA genotype were more frequent in individuals with mucositis (p= 0.02; RR = 0.60; CI = 0.387 - 0.813). The severity of the disease was mainly observed in younger patients (median = 9 years; p=0.02). Patients with severe oral mucositis presented lower leukocytes count (median = 2.150 mm3) compared to patients with the mild/moderate form (median = 4.200 mm3; p=0.03). Female patients and each 10,000-platelet increase were protective factors against the onset of oral mucositis (p=0.02). It is concluded that rs2231142 polymorphism increases the likelihood of oral mucositis and younger patients and patients with low leukocytes counts are more likely to develop severe form.